2001
DOI: 10.1103/physrevlett.86.5023
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic Scaling in Nuclear Reactions

Abstract: A three parameter scaling relationship between isotopic distributions for elements with Z< or =8 has been observed. This allows a simple description of the dependence of such distributions on the overall isospin of the system. This scaling law (termed isoscaling) applies for a variety of reaction mechanisms that are dominated by phase space, including evaporation, multifragmentation, and deeply inelastic scattering. The origins of this scaling behavior for the various reaction mechanisms are explained. For mul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
442
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 337 publications
(462 citation statements)
references
References 23 publications
19
442
0
Order By: Relevance
“…In recent years isospin effects on fragment production have been discussed in terms of an isoscaling behaviour, revealed first in multifragmentation data [74,170]. It was experimentally observed that comparing two different reactions, one neutron rich (label 2) and one neutron poor (label 1), the ratio between the yields of a given N, Z isotope R 21 = Y 2 (N, Z)/Y 1 (N, Z) follows the relation:…”
Section: Isoscaling Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…In recent years isospin effects on fragment production have been discussed in terms of an isoscaling behaviour, revealed first in multifragmentation data [74,170]. It was experimentally observed that comparing two different reactions, one neutron rich (label 2) and one neutron poor (label 1), the ratio between the yields of a given N, Z isotope R 21 = Y 2 (N, Z)/Y 1 (N, Z) follows the relation:…”
Section: Isoscaling Analysismentioning
confidence: 99%
“…This effect is certainly present but it appears overestimated within the grand canonical picture. In the same scheme the isoscaling parameters, being related to the difference of neutron and proton chemical potentials, can provide an evaluation of the symmetry term of the EOS in dilute matter [170,120]. Very low values are deduced, with a large uncertainty due to the determination of the temperature of the equilibrated source.…”
Section: Isospin Distillation and Isoscalingmentioning
confidence: 99%
See 3 more Smart Citations